2010
DOI: 10.3109/14015430903582128
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between subjective self-rating and objective voice assessment measures

Abstract: This cross-sectional study highlights that patients' self-perception of a voice problem is related to their difficulty in sustaining controlled loudness and adequate glottic closure rather than in controlling frequency irregularity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Their diagnosis still presents numerous challenges to both clinicians and researchers [1][2][3]. Occupational dysphonia is complex in nature and requires multidimensional management [4][5][6]. Given that voice is a key tool for professional voice users, its disorders may result in significant communication handicap for those affected [1,7].…”
Section: Introductionmentioning
confidence: 99%
“…Their diagnosis still presents numerous challenges to both clinicians and researchers [1][2][3]. Occupational dysphonia is complex in nature and requires multidimensional management [4][5][6]. Given that voice is a key tool for professional voice users, its disorders may result in significant communication handicap for those affected [1,7].…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that a useful tool for measuring voice use and voice rest would demonstrate convergent validity (i.e., an association between self‐reported voice use and measured phonation in normal subjects). We expected a moderate strength of association based on other studies of relationships between subjective and objective ambulatory measures . We also hypothesized that such a tool would demonstrate significantly decreased voice use (phonation percent) and loudness (sound level) in patients on voice rest after treatment.…”
Section: Introductionmentioning
confidence: 98%
“…Central to aerodynamic assessment is the measurement of subglottal pressure (P s ), a parameter valuable in isolation that is also required for determination of vocal efficiency, laryngeal airway resistance (R L ), phonation threshold pressure, and phonation threshold power. Aboras et al measured a wide range of acoustic and aerodynamic parameters and found that P s was the only parameter predictive of patients’ self-perception of dysphonia (6). Routine clinical measurement of P s , therefore, may be valuable.…”
Section: Introductionmentioning
confidence: 99%